Knowledge of reproductive health in postpartum adolescents treated at the National Hospital Cayetano Heredia 1994. - Cueca, Alberto (2015)
OBJECTIVE: To determine knowledge on reproductive health of adolescent mothers and the determinant factors involved. DESIGN: Comparative study done at the Obstetrical Service, Cayetano Heredia National Hospital. Inquiry to 183 post-partum adolescents, between September 1 and December 15, 1994. RESULTS: 25.7% had no adecuate prenatal control, 60,7% did not attend a prenatal talk, 51% pregnancies were not wished, 86.8% knew some contraceptive method, but only 42, 1 % had used it in some occassion; from these, 50,6% used natural methods, but 46% inapproppiately; 63,9% feared the use of contraceptive methods, especcially the modern ones. Time between first sexual relation and beginning of pregnancy was one year or less in 50,4%; 87,9% knew about sexually transmitted diseases, mainly AIDS and 55,2% knew about fecundation. CONCLUSION: The more education and number of prenatal talks, better knowledge on reproductive health.